2021
DOI: 10.1016/s1473-3099(20)30919-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the global number of tuberculosis survivors: a modelling study

Abstract: BackgroundPeople who survive tuberculosis continue to experience clinical and societal consequences after recovery, including increased risks of recurrent tuberculosis, premature death, reduced lung function, and ongoing stigma. We aimed to describe the magnitude of this issue by estimating the number of tuberculosis survivors, who could be amenable to intervention. MethodsWe estimated the number of people who developed tuberculosis during 1980-2019 and survived until 2020. Numbers surviving treatment were bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 30 publications
2
71
0
3
Order By: Relevance
“…Vaccination is an effective method to achieve herd immunity and thereby curb the catastrophic effects of the COVID-19 pandemic worldwide. In line with previous literature, in this sample, vaccine hesitancy was influenced by referent health authority of physicians and by contemporary health issues, COVID-19 beliefs, and the perception that the COVID health risk had been exaggerated [ 7 , 21 ]. The complexity of attitudes underlying vaccine hesitancy and the potential for a vaccine to mitigate the COVID-19 pandemic underscore the urgent need to accurately measure and address the issues influencing vaccination uptake in populations at highest risk of severe COVID-19, such as PWH with comorbid conditions.…”
Section: Discussionsupporting
confidence: 77%
“…Vaccination is an effective method to achieve herd immunity and thereby curb the catastrophic effects of the COVID-19 pandemic worldwide. In line with previous literature, in this sample, vaccine hesitancy was influenced by referent health authority of physicians and by contemporary health issues, COVID-19 beliefs, and the perception that the COVID health risk had been exaggerated [ 7 , 21 ]. The complexity of attitudes underlying vaccine hesitancy and the potential for a vaccine to mitigate the COVID-19 pandemic underscore the urgent need to accurately measure and address the issues influencing vaccination uptake in populations at highest risk of severe COVID-19, such as PWH with comorbid conditions.…”
Section: Discussionsupporting
confidence: 77%
“…One study reported that 363 million people in 190 countries developed TB between 1980 and 2019, of whom 155 million were alive in 2020. 4 This indicates that the number of TB survivors alive in 2020 is more than 10 times the estimated annual TB incidence. Three definitions of sarcopenia: Sarcopenia_BMI = ASM (kg) / BMI (kg/m 2 ) was defined as < 0.789 in men or < 0.512 in women, according to the FNIH recommendation using ASM/BMI ratio; Sarcopenia_weight = ASM (kg) / weight (%) was defined as < 29.0 in men or < 22.9 in women, according to the 2008-2011 KNHANES data; Sarcopenia_height = ASM (kg) / height 2 was defined as 7.0 kg/m 2 in men or < 5.4 mg/m 2 in women, according to the AWGS recommendation using height-adjusted skeletal muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of tuberculosis across the life course, evidenced by increased all-cause mortality post infection 37 and post-tuberculosis lung disease, 38 in addition to implications for future test result interpretation, specifically Xpert MTB/RIF and Xpert MTB/RIF Ultra, also necessitate this. Moreover, patients with presumed tuberculosis subsequently found not to have tuberculosis will include some of the estimated 155 million patients globally alive today post tuberculosis 39 and provide an opportunity to identify them allowing for provision of on-going care.…”
Section: Discussionmentioning
confidence: 99%